Where Does Russia Fit into the Global Software Industry? - Cusumano, Michael A. (Communications of the ACM, 2006)
This article presents the author's exploration of how Russia's nascent software industry measures up to other countries. The first annual Software Engineering Conference-Russia was held in Moscow, and had more than 500 attendees. The conference was sponsored by Intel, Borland, Microsoft, Telelogic, IBM, and Siemens. It was organized by RUSSOFT, the Russian National Association of Software Development Companies, and RUSSEE, a 20-person venture based in Moscow that is actively engaged in education and consulting on best practices in software development. The author says that the main concern of most of the European programmers, he has worked, is with excellence and elegance in program architecture, design, and construction, incorporating the latest technologies, or building custom systems for the various European markets. He says that programmers and managers in Japan, where he lived for seven years, largely treated software as a problem in production. He says that there is something unique about the U.S.-based software business. The U.S. has great university departments and programmers who are second to none in their knowledge of the science. He argues that Russia will have great difficulty escaping the paradigm of treating software primarily as a science.